Visible Light Activated Radical Denitrative Benzoylation of β‐Nitrostyrenes: A Photocatalytic Approach to Chalcones. Issue 7 (16th February 2018) - Tripathi, Shubhangi; Kapoor, Ritu; Yadav, Lal Dhar S.
Abstract: A metal‐free, convenient photocatalytic approach to chalcones from β ‐nitrostyrenes and benzaldehydes via a radical denitrative benzoylation pathway is reported. The salient features of the protocol include the utilization of visible light as an inexpensive and ecosustainable energy source, N ‐hydroxyphthalimide (NHPI) as a reusable organophotocatalyst and acetonitrile as an acceptable green solvent to afford chalcones in excellent yields at room temperature in a one‐pot procedure. Notably, this is the first application of β ‐nitrostyrenes as readily available substrates for chalcone synthesis and the first example of photocatalysis in this field. Abstract :